2021
DOI: 10.3389/fnins.2020.631025
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Sleep Duration and Sleep Efficiency Were Independently Associated With Frequent Nightmares in Chinese Frontline Medical Workers During the Coronavirus Disease 2019 Outbreak

Abstract: ObjectivesNightmares were related to emotion and behavioral problems and also emerged as one of the core features of post-traumatic stress disorder (PTSD). Our study aimed to investigate the associations of frequent nightmares with sleep duration and sleep efficiency among frontline medical workers in Wuhan during the coronavirus disease 2019 (COVID-19) outbreak.MethodsA total of 528 health-care workers from the province of Fujian providing medical aid in Wuhan completed the online questionnaires. There were 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
1
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 45 publications
2
21
1
1
Order By: Relevance
“…The occurrence of nightmares among the general population increased significantly after experiencing the COVID-19 pandemic, the greatest public health crisis since the influenza pandemic of 1918 ( Kilius et al, 2021 Musse et al, 2020 ; Scarpelli et al, 2021 ;). Approximately one-third to one-half of frontline hospital workers suffered from nightmares during the COVID-19 outbreak ( Lin et al, 2020 Stewart et al, 2021 ;), which was higher than 15.6% in the present study. One possible reason for this difference is that our study was conducted 1-3 months after the major outbreak timepoint of COVID-19 in Wuhan.…”
Section: Discussioncontrasting
confidence: 70%
“…The occurrence of nightmares among the general population increased significantly after experiencing the COVID-19 pandemic, the greatest public health crisis since the influenza pandemic of 1918 ( Kilius et al, 2021 Musse et al, 2020 ; Scarpelli et al, 2021 ;). Approximately one-third to one-half of frontline hospital workers suffered from nightmares during the COVID-19 outbreak ( Lin et al, 2020 Stewart et al, 2021 ;), which was higher than 15.6% in the present study. One possible reason for this difference is that our study was conducted 1-3 months after the major outbreak timepoint of COVID-19 in Wuhan.…”
Section: Discussioncontrasting
confidence: 70%
“…One study on healthcare workers found that individuals with frequent nightmares during the pandemic reported higher worry about being infected and family’s infection of COVID-19, lower confidence in being cured if infected and sense of competence, a greater percentage of poor mental health, higher General Health Questionnaire score, reduced sleep duration, higher diurnal sleepiness, and poorer sleep quality ( Lin et al, 2021 ). Moreover, reduced sleep duration and reduced habitual sleep efficiency were associated with frequent nightmares ( Lin et al, 2021 ). In a small group of narcoleptic patients, nightmare frequency was related to the female gender, longer sleep duration, higher intra-sleep wakefulness, and sleepiness ( Scarpelli et al, 2021b ).…”
Section: Resultsmentioning
confidence: 99%
“…Studies have also found associations between the pandemic and dream quality and quantity; individuals reported more negative emotions in dreams (Schredl and Bulkeley, 2020;Gorgoni et al, 2021), increased pandemic-related dreams (MacKay and DeCicco, 2020;Pesonen et al, 2020). Among frontline medical workers, reduced sleep duration and efficiency were linked to frequent nightmares during the COVID-19 pandemic (Lin et al, 2021), highlighting the possibility of burnout and/or development of PTSD symptoms. Taken together with existing epidemiolocal studies showing the relation between sleep disturbances and negative health outcomes, such as obesity (Buxton and Marcelli, 2010), impaired metabolic health (Schmid et al, 2015), type 2 diabetes (Knutson et al, 2006;Lee et al, 2017), andPTSS (McCall et al, 2019;Richards et al, 2019), the current pandemic may have brought about additional adverse psychological and health consequences, beyond those directly linked to the virus outbreak itself.…”
Section: Discussionmentioning
confidence: 99%